FROM DRILL TO SKILL: EXPLORING THE POTENTIAL OF AUDIOLINGUAL DRILL IN SHAPING SPEAKING SKILL - Magvirah Octasary; Lebagi, Destrin; Mbau, Anitha Thalib (Jurnal Pesastra (Pendidikan Bahasa dan Sastra), 2024)
This study aims to test the effectiveness of the audiolingual drill method in improving the English speaking ability of tenth grade students at MA Al-Izzah As'Adiyah, consist of 2 parallel classes. This study used quantitative research, methods that employ numerical data for clarifying conclusions. This research design allowed you to compare two groups of students, namely, the experimental group that received audio-lingual drill treatment and control group that received the conventional learning method. The primary outcome of this study indicated that although there was no discernible increase in terms of accuracy or grammar, students in the experiment group spoke with greater confidence. The study's findings support the notion that, when it comes to helping students become better communicators, the audio lingual drill method outperforms the traditional learning approach.